Responses to a 120 min reserve team soccer match: a case study focusing on the demands of extra time - Russell, M.; Sparkes, W.; Northeast, J.; Kilduff, L. P. (Journal of Sports Sciences, 2015)
The movement demands of the soccer extra time period are unknown despite the importance of this period of play. Data are presented for five English Premier League reserve team players who wore GPS (10 Hz) monitors during an official soccer match that required extra time to be played. Countermovement jump performance (peak power output (PPO) and jump height) and creatine kinase (CK) concentrations were assessed before (-24 h; baseline) and after (+24 h, +48 h) match play. Players covered 14,106 ± 859 m (109 ± 7 m/min) throughout the game. From 90 to 120 min, 3213 ± 286 m were covered and 12 ± 6 sprints, 221 ± 14 accelerations and 207 ± 16 decelerations occurred. From 105 to 120 min, acceleration and deceleration parameters reduced by >10% compared to the opening 15 min. At +24 h and +48 h, PPO reduced by 416.1 ± 199.9 W (10.9% ± 4.4%) and 155.1 ± 34.8 W (4.1% ± 0.8%), jump heights decreased by 0.064 ± 0.046 m (17.8% ± 11.2%) and 0.025 ± 0.009 m (7.4% ± 3.2%), whereas CK increased by 586.6 ± 85.1 µ/l (236% ± 92%) and 266.8 ± 134.7 µ/l (107% ± 89%) versus baseline, respectively. Physical performance markers reduced throughout match play and countermovement jump performance was impaired, while CK remained elevated, for at least 48 h after the game. Interventions which maintain performance throughout a game and which enhance recovery in the days after 120 min of soccer match play warrant further investigation.